Taxonomic inventory and range of distribution of parrotfishes (perciformes scraidae) in Samal Island, Davao Gulf - Barez, Gyne Faith Carumba (2009)
Parrotfishes (Family Scaridae) found along the coast of Samal and Talicud Islands, Davao Gulf were investigated. Market collection of the specimens was done weekly from June to July 2008. While fish visual census sampling was conducted once in the MPAs of Sanipaan, Coral Garden, Balet and Aundanao in March, August and December 2008, respectively. Based from the market survey and the fish census, a total of sixteen species of parrotfishes were recorded which include the following: cetoscarus bicolour, Chlorurus bleekeri, C. capistratoides, C. japanensis, C. microrhinos, C. soridus, scarus dimidiatus, S. flavipectoralis, S. ghobban, s. hypselopterus, S. psittacus, S. niger, S. Quoyi, S. rivulatus, S. rubroviolaceus, and S. trocolour. One individual of C. capistratoides was obtained during the market collection, is a non-native to the Philippines and only distributed in the Maldives, Indian Ocean, and the western and central seas of Indonesia. Market survey for size at sexual maturity was only established in two species, namely: S. rivulatus and S. tricolour at 13.20 cm. TL and 20.70cm TL, respectively. Of the 69 individuals observed during the fish visual census, dominant species observed were S. rivulatus (30.4%), unidentified Scarid species no. 2 (28.99%) C. sordidus (26.09%) and S. dimidiatus (7.25%). The least number of individuals observed were S. quoyi, S. niger, Scarus sp. and an unidentified Scarid no. 1 and 3 (1.45% each). Moreover, 75.36% of the number of individuals was detected in Aundanao MPA. The exposure to wave action and high relief measurement, and being a no-take zone greatly favored high abundance of parrotfishes in this area. Out of the detected parrotfishes during fish visual census, C. sordidus appeared to be the most widely distributed species being found in all four sampling sites
Thesis, Undergraduate (BS Biology)-U.P. Mindanao
Keywords: Sexual maturity; Parrotfishes; Fishes -- Visual census; Fishes; Family Scaridae; Class Actinopterygii (ray-finned fishes).; Scarids; Coral reef fishes; Gonad classification; Species identification; oucher specimens; Reproductive biology; Functional morphology; Taxonimic classification; Samal island; Samal island -- Davao del Norte -- Mindanao, Philippines; Davao Gulf